Estresse metabólico em células endometriais e espermatozoides bovinos: efeito de ácidos graxos não esterificados e hipocalcemia - Vieira, Camila Cupper (2024)
In the transition period, which comprises three weeks before and three weeks after calving, bovine females develop a negative energy balance (BEN). The BEN is the period in which the energy demands are greater than the nutritional intake, leading to the intense mobilization of body reverses, which is reflected in the increase in blood levels of nonesterified fatty acids (NEFA) and β-hydroxybutyrate (BHB), and decreased insulin and glucose concentrations. Studies have shown that these blood alterations are reflected in the oviductal and uterine microenvironment of cattle. Therefore, it is important to evaluate how these changes can affect sperm when they meet the female's reproductive tract. Therefore, the objective of the first work of this thesis is to evaluate the effects of NEFA on the morphology, kinetics, and oxidative status of bovine spermatozoa in vitro. The results demonstrate that different concentrations of palmitic acid (PA), stearic acid (SA), and oleic acid (OA) do not alter sperm kinetics, morphology, or sperm oxidative status. The objective of the second work of this thesis is to evaluate the effects of transient subclinical hypocalcemia on the uterine insulin signaling pathway in dairy cows. It is known that postpartum dairy cows have hypocalcemia and that this condition is a risk factor for uterine infections and can culminate in changes in insulin signaling. The results first demonstrated that our protocol for inducing hypocalcemia with 5% EDTA solution was effective in reducing circulating ionized calcium concentrations. We observed that blood levels of glucose, insulin, and NEFA were not altered by hypocalcemia, while BHB levels were reduced. Regarding the expression of genes related to the insulin and glucose signaling pathway, INSR, IRS1, IGF, GLUT1, and GLUT3, hypocalcemia did not negatively affect any of the genes evaluated. From the data obtained with this thesis, it was possible to determine that NEFA in the tested conditions does not negatively affect the viability of bovine spermatozoa and that transient subclinical hypocalcemia does not alter the insulin signaling pathway in the uterus of dairy cows.